Recent patents in solar energy collectors and applications - Kalogirou, Soteris A. (My University, 2007)
Solar energy collectors are special kind of heat exchangers that transform solar radiation energy to internal energy of the transport medium. The solar collector is the major component of any solar system. There are basically two types of solar collectors: non-concentrating or stationary and concentrating. The latter require some kind of tracking mechanism so as to allow the collector to follow the apparent movement of the sun with certain accuracy. This paper reviews various recent patents in both types of collectors, tracking mechanisms and various applications. The patents reviewed concern a period extending from the years 2002 up to date. The patents included in this review refer mainly to solar collectors which include flat plate, parabolic troughs and central receiver collectors, whereas a number of patents concern the development of mechanisms for tracking the sun. The applications concern mainly integrated collector storage, water heating systems, solar desalination, absorption cooling, air conditioning and refrigeration. The list of patents reviewed is by no means complete or extensive it shows however the extent of the subjects covered in patents in this area during the last four years. The paper concludes with a description of the future developments expected in the subjects covered.
Keywords: Flat plate collectors; Parabolic trough collectors; Central receiver systems; Solar tracking mechanism; Solar water heating; Solar cooling; Solar desalination